An Evaluation of Academic Performance in Light of Some TQM Requirements at the Faculty of Education and Languages - Amran, Republic of Yemen - Fahd Saleh AL- Mamari (University of Science and Technology, Yemen, 2016)
Abstract: The aim of this research was to evaluate academic performance in the Faculty of Education and Languages in the city of Amran, by applying some of the requirements of TQM from the viewpoint teachers of the college, and impact of (sex , specialty, qualification, experience)  on their assessment of the performance, using the descriptive method. A questionnaire of (79) items distributed over seven themes was designed and distributed to   all members of the population which were (100). (100). The respondents, whose number was 76, were (32) PhD holders, (14) MA holders and (30) BA holders.  After using the SPSS statistical package, the analysis revealed the following: 1- the Pan performance on average ( 2.18) from (05 ); evaluation (weak). And as areas ;the area ( 5 ); quality of faculty members and their assistants ; got ( acceptable), average (2.64 );  and got the area ( 4); quality  of guidance and counseling programs - on average (1.80) evaluation (non-existent), and got the rest areas, on average between (2.30 - 1.85); rating (weak).Finally; there are not any standard; rating (good, very good). According to the standards got (25) criterion; (31.7%) On the evaluation of the (non-existent), and (34) criterion; (43%) Evaluation of (weak), and (20) standards, ( 25.3 %) evaluation (acceptable), and one standard; got( 1.32% ) On the evaluation of (good); the highest rating in the search. 2 - there are signifcant differences at (α = 0.05) due to sex, in the area (6) ; research and scientific activities ; fore females , and experience; in three areas; ( 7, 5 , 3); ( calendar system of students, faculty, labs ); for the least of the five years experience, and qualifier;  and in the area (7); quality of labs; for doctoral and University graduate, and the lack of differences in other areas. 3 - In the light of the results there is a number of recommendations and proposals to achieve quality assurance and accreditation at the Faculty of Education Imran.